Chiral Cu(II) salen complexes catalyzed aerobic oxidative biaryl coupling-probing the reaction by EPR - Sabarinathan, Subbaramanian; Vasuki, Gnanasambandam; Rao, Pillutla Sambasiva (European Journal of Chemistry, 2010)
Aerobic oxidative coupling of 2-naphthol to 1,1’-binaphthyl-2,2’-diol has been achieved using chiral/achiral copper salen complexes as catalyst. Moderate enantioselectivity was obtained for the reaction of 2-napthol with a coordinating substituent with a chiral salen complex. Unsubstituted 2-naphthol resulted in racemic 1,1’-binaphthyl-2,2’-diol only with all chiral complexes. Electron paramagnetic resonance spectroscopy has been used to understand the factors influencing the asymmetric induction.